Long-Term Durability and Mechanical Performance of Alkali-Activated, Slag Cements - Pavia, Sara; Alelweet, Omar (My University, 2021)
Alkali activated (AA) cements are considered less harmful to the environment than Portland cements (PC), as they consist of a silicate waste in lieu of a PC clinker, and this implies lower green-house gas emissions and no exhaustion of unrenewable material sources. This paper investigates cements made with ground granulated blast furnace slag (GGBS) activated with sodium hydroxide (NaOH) and sodium silicate (Na2SiO3), both combined and separately, and cured at 20 and 60°C. The 28-day and 270-day strengths are compared. Furthermore, the materials are subject to accelerated weathering tests (wet-dry, salt crystallization and freeze-thaw cycles), and the strength loss, mass loss and macroscopic changes after cycling studied. The GGBS is characterized using analytical techniques. Previous work concluded that it complies with standard requirements for the use of slags in concretes and mortars (Alelweet and Pavia 2019). The results indicate that the strength tends to increase between 28 and 270 days. The strength increase at late ages does not conform with former authors such as Collins and Sanjayan (2001) who found strength reductions at late ages due to microcrack networks that appear at late age. Increasing the curing temperature enhances mechanical strength at 28 days when the activator is Na2SiO3 + NaOH agreeing with Fernández-Jiménez et al.1999. In contrast, at late ages (270 days) despite occasional contradictions, increasing the curing temperature does not generally enhance mechanical strength also agreeing with former literature. The strength loss due to artificial ageing is highly inconsistent as some of the weathered specimens show greater strength than the unweathered (control) ones. However, the Na2SiO3/NaOH activated GGBS materials clearly show the greatest resilience to the effects of frost, thermal/moisture cycles and salt action as they remained intact after cycling, while both the NaOH and the Na2SiO3 activated GGBS materials developed slight decay including efflorescence, swelling and cracks. The microstructural (SEM) study of the best performers (Na2SiO3+NaOH activated, GGBS materials) revealed areas of unreacted GGBS particles bound with scattered silica cements alternating with abundant alumino-silicates. The SEM image (left) shows the isometric and tabular alumino-silicates in the Na2SiO3+NaOH activated GGBS materials.
Global Summit on Civil, Architectural, and Environmental Engineering (GSCAEE2021)
Keywords: GGBS; Alkali activation; Freeze-thaw; Salt crystallization; Wet-dry cycles; 270-day strength